Quattro parole fondamentali per la vita della mente - Fiori Nastro, Paolo; Fagioli, Luca (Il sogno della farfalla, 2008)
The article proposes a broad reflection around four words which are crucial for psychiatric and psychological research: conscious memory, non-conscious memory, separation and transformation and the way these concepts differ from and relate to each other. Among the themes developed is the passage from sleep-wakefulness and wakefulness-sleep, the distinction between the disappearance fantasy and the annulment drive and the recreation of the preverbal dimension of the first year of life.